Inclusion of a phytogenic bend in broiler diet as a performance enhancer and anti-aflatoxin agent: Impacts on health, performance, and meat quality - Armanini E.H.* (2021)
© 2021 Elsevier LtdThe objective of this study was to determine whether a phytogenic blend (PB), formulated based on organic acids, tannins, curcumin, and essential oils, could replace the antimicrobials commonly used as growth promoters in the poultry industry without compromising zootechnical performance, health, or meat quality. In addition, our goal was to report the anti-aflatoxin effect of this phytogenic blend. Four treatments were used: TC, or control; T250, T500, and T1000, representing test doses of 250, 500, 1000 mg PB/kg of feed, respectively, or a 34-day experiment (initial and growth phases). On day 22 of the study and age of the birds, 500 ppb of aflatoxin was included in the diet to represent an intestinal challenge and to evaluate the growth-promoting effects of PB. In the initial phase (up to 21 days), there were no differences between groups in weight gain, feed intake, or feed conversion. After adding an aflatoxin-contaminated feed, doses of 250 and 500 mg/kg minimized the adverse effects on feed consumption and feed conversion caused by aflatoxin; but 1000 mg/kg did not differ between groups. In birds that consumed PB (T250, T500, and T1000) compared to the control, there were the following changes: 1) lower counts of heterophiles, lymphocytes, and monocytes; 2) lower lipid peroxidation and high non-protein thiols levels in breast meat; 3) lower bacteria counts in broiler litter; and 4) lower ALT levels. Greater intestinal villus/crypt ratios were observed at T250 and T500. The dose of 250 mg/kg reduced saturated fatty acids and increased unsaturated fatty acids. The chemical-physical composition of the meat did not differ between treatments. The findings suggest that the addition of a PB has a high potential to improve performance for chickens in the growing stage and minimize the adverse effects of aflatoxicosis.